(untitled) (Temporalis, 2026)
This article aims to apprehend the theoretical construction of the "law of combined development" in Leon Trotsky’s thought, considering the connection between this elaboration and the course of the political-ideological struggle in which its author was immersed. Such analysis also seeks to determine the established content for the formula of the "law of combined development", its link with the "theory of permanent revolution" and the polemic with the "theory of socialism in one country". To this end, a bibliographic research was carried out, supported by the survey of the theme in the work of the aforementioned author, which focused his studies on the history of the Russian Revolution and the texts dedicated to the theoretical-political struggle around the course of the revolution. Finally, this article includes a dialogue between the aforementioned formulation and the reading offered by George Novack in the 1950s about the "law of unequal and combined development".